In-Situ Computed Tomography of Particle Microcracking and Electrode Damage in Cycled NMC622/Graphite Pouch Cell Batteries. Issue 8 (1st August 2022) - Bond, Toby; Gauthier, Roby; Gasilov, Sergey; Dahn, J. R.
Abstract : Mechanical degradation of electrode materials is an important failure mode in lithium-ion batteries. High-energy-density cathode materials like nickel-rich NMC (LiNix Mny Coz O2 ) undergo significant anisotropic volume expansion during cycling that applies mechanical stress to the material. Computed tomography (CT) of cells can be used to image cell-level and electrode-level changes that result from long-term cycling, without the need for cell disassembly or destructive sampling. Previous work by our group has used synchrotron CT to show cathode thickness growth and depletion of liquid electrolyte after long-term (>2 years) cycling of polycrystalline NMC622/graphite cells. These phenomena were attributed to cathode microcracking, but direct evidence of this was not available at the time. In this study, we present in-situ, sub-micron CT of these unmodified pouch cells, providing new insights into the morphological changes occurring at the particle level. These results confirm that extensive microcracking and dramatic morphological changes are occurring in the cathode that were not previously observed. Combined with the cell-level and electrode-level scans presented previously, this study provides a complete, multi-scale picture of cathode microcracking and how its effects propagate throughout the cell.